Pencegahan Kekerasan Seksual di Sekolah: Program Kolaboratif oleh Departemen Forensik dan Medikolegal, Fakultas Kedokteran Universitas Andalas: Pencegahan Kekerasan Seksual di Sekolah: Program Kolaboratif oleh Departemen Forensik dan Medikolegal, Fakultas Kedokteran Universitas Andalas - Susanti, Rika; Windasari, Noverika; Sukma, Muthia; Hidayat, Taufik; Manela, Citra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Sexual violence among adolescents constitutes a growing public health and human rights concern globally, including within educational settings in Indonesia. This study aimed to evaluate the effectiveness of a structured educational intervention in improving students’ knowledge and awareness of sexual violence at SMA Xaverius Bukittinggi. A quasi-experimental study with a one-group pretest–post-test design was conducted in September 2025. Participants completed a baseline assessment, followed by an intervention consisting of lectures, case-based learning, and facilitated discussions, and subsequently a post-intervention evaluation. Outcome measures focused on knowledge of sexual violence typologies, reporting mechanisms, and early detection indicators. Baseline results revealed substantial knowledge gaps across all assessed domains. Post-intervention findings demonstrated a significant improvement in students’ understanding, particularly in recognizing forms of sexual violence, identifying appropriate reporting pathways, and detecting early warning signs. The increase in pretest and post-test scores indicates the effectiveness of the intervention in enhancing both awareness and conceptual comprehension. These findings support the implementation of targeted, school-based educational programs as a practical strategy for sexual violence prevention. Regular and sustained interventions are recommended to reinforce knowledge retention, promote early identification, and foster safer educational environments. Institutionalizing annual programs at SMA Xaverius Bukittinggi may contribute to long-term prevention and student empowerment.